2020
DOI: 10.1021/acs.jproteome.0c00337
|View full text |Cite
|
Sign up to set email alerts
|

Danger in the Canopy. Comparative Proteomics and Bioactivities of the Venoms of the South American Palm Pit ViperBothrops bilineatusSubspeciesbilineatusandsmaragdinusand Antivenomics ofB. b. bilineatus(Rondônia) Venom against the Brazilian Pentabothropic Antivenom

Abstract: We report a structural and functional proteomics characterization of venoms of the two subspecies (Bothrops bilineatus bilineatus and B. b. smaragdinus) of the South American palm pit viper from the Brazilian state of Rondônia and B. b. smaragdinus from Perú. These poorly known arboreal and mostly nocturnal generalist predators are widely distributed in lowland rainforests throughout the entire Amazon region, where they represent an important cause of snakebites. The three B. bilineatus spp. venom samples ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 75 publications
5
20
1
Order By: Relevance
“…The data also showed a 'PLA 2 connection' between the B. atrox population of Puerto Ayacucho (Venezuelan Amazonia, 3) and the Colombian Magdalena Medio Valley B. asper population (1) (Figure 3B). This finding is consistent with a model of dispersal of the ancestors of B. asper along a northeast to northwest path, presumably through corridors between the Venezuelan Cordillera de Mérida and the Colombian Cordillera Oriental and Sierra de Perijá and Sierra Nevada de Santa Marta (asterisk in Figure 3A [40] revealed that the two Brazilian taxa share an identical PLA 2 molecule between themselves but not with Peruvian B. b. smaragdinus (Figure 4B). This seemingly unusual result only found a logical explanation when the origin of the poisons donor lineages was investigated.…”
Section: Tracing Dispersal Patterns Of the Wide-ranging Species Bothrops Atrox And B Aspersupporting
confidence: 90%
“…The data also showed a 'PLA 2 connection' between the B. atrox population of Puerto Ayacucho (Venezuelan Amazonia, 3) and the Colombian Magdalena Medio Valley B. asper population (1) (Figure 3B). This finding is consistent with a model of dispersal of the ancestors of B. asper along a northeast to northwest path, presumably through corridors between the Venezuelan Cordillera de Mérida and the Colombian Cordillera Oriental and Sierra de Perijá and Sierra Nevada de Santa Marta (asterisk in Figure 3A [40] revealed that the two Brazilian taxa share an identical PLA 2 molecule between themselves but not with Peruvian B. b. smaragdinus (Figure 4B). This seemingly unusual result only found a logical explanation when the origin of the poisons donor lineages was investigated.…”
Section: Tracing Dispersal Patterns Of the Wide-ranging Species Bothrops Atrox And B Aspersupporting
confidence: 90%
“…These fractions comprise endogenous tripeptide inhibitors of snake venom metalloproteinases (SVMPi) [70][71][72][73], 10-12 amino acid residue bradykininpotentiating-like peptides (BPPs) [72,74,75], and disintegrin (DIS) molecules. Among these early-eluting venom components only disintegrin are immunogenic [76][77][78][79], and therefore, the immunoretained fraction may comprise this class of toxins, which in B. ayerbei [28], B. asper, and B. rhombeatus [32] represent 2.3-5.6% of their total venom proteins. On the other hand, chromatographic fractions 4-7, eluted between 10-30 min, comprised disintegrin-like/ cysteine-rich (DC) fragments of PIII-SVMPs, phospholipase A 2 (PLA 2 ) , molecules, cysteinerich secretory proteins (CRISP) and serine proteinases (SVSP), and were immunocaptured at maximal immunoaffinity column binding capacity with average efficacy of 62% (B. asper), 3).…”
Section: Immunoreactivity Profile Of Antivenoms: Third-generation Antivenomicsmentioning
confidence: 99%
“…Biogeographic studies PLOS NEGLECTED TROPICAL DISEASES support B. asper as the first species complex to split from the B. atrox group in the Pliocene, around 3.02-2.32 Mya [90], and cladogenesis into lineages began soon thereafter, towards the end of the Pliocene [23]. The realization of the existence of large immunological conservation across Bothrops phylogeny emerged also from studies of the paraspecific effectiveness of the pentabothropic polyvalent antivenom SAB (soro antibotrópico pentavalente) produced by Instituto Butantan (São Paulo, Brazil) [52,76,79,[91][92][93][94] using a pool of venoms from B. jararaca (50%), B. jararacussu (12.5%), B. moojeni (12.5%), B. alternatus (12.5%) and B. neuwiedi (12.5%) [95,96]. Further, an assessment of the ability of seven polyspecific antivenoms, produced in Argentina, Brazil, Perú, Bolivia, Colombia and Costa Rica using different immunization mixtures, to neutralize lethal, hemorrhagic, coagulant, defibrinogenating and myotoxic activities of the venoms of B. diporus (Argentina), B. jararaca (Brazil), B. matogrossensis (Bolivia), B. atrox (Perú and Colombia) and B. asper (Costa Rica) also showed a pattern of extensive cross-neutralization of all the venoms tested, with quantitative differences in the values of the effective doses of the antivenoms [93,97].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Snake venom metalloproteinases (SVMPs) were the most abundant toxins with the predominance of the PIII-class; snake venom serine proteinases (SVSP), C-type lectin-like proteins (CTL), phospholipases A2 (PLA2), cysteine-rich secretory proteins (CRISP), and L-amino acid oxidases (LAAO) were also detected in all samples, representing the major components of their venom proteomes. Bradykinin-potentiating-like peptides (BPPs) and the tripeptide inhibitors of SVMPs were also abundant in the three samples analyzed in one of the studies ( 83 , 84 ). Snake venom vascular endothelial growth factor, nerve growth factor, 5′-nucleotidase, phosphodiesterase, phospholipase B, and others were also detected in minor amounts in venom samples ( 83 , 84 ).…”
Section: Bothrops Bilineatus Snake Venommentioning
confidence: 99%
“…Only a few reports on the characterization of B. bilineatus venom-derived components are available. However, two recent venomics studies have been published, and contributed with important evidence about the composition of venom from B. bilineatus subspecies bilineatus and smaragdinus ( 83 , 84 ). The authors analyzed samples of pooled venoms from Peruvian B. b. smaragdinus specimens, and also pooled venoms of two B. b. smaragdinus specimens originally from Rondonia state, Brazil, and the venom from a single specimen of B. b. bilineatus from Rondonia state that had been kept frozen and crystalized for more than 10 years.…”
Section: Bothrops Bilineatus Snake Venommentioning
confidence: 99%